Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Neonatal Pulmonology, Neonatal Respiratory Support, Resuscitation" - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Neonatal Pulmonology, Neonatal Respiratory Support, Resuscitation" ABS 1. HOW SAFE IS NASAL CANNULAE OXYGEN THERAPY DURING NEONATAL TRANSPORT? • A. Brunton, J. O’Shea, A. Jackson ABS 2. WEANING PREMATURE INFANTS FROM NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE – CURRENT PRACTICE IN GERMANY • A. Kidszun, C. Arnold, J. Winter, C. Whybra-Trümpler, E. Mildenberger ABS 3. TIMING OF KEY EVENTS IN NEONATAL RESUSCITATION • A. Heathcote, J. Jones, P. Clarke ABS 4. COMPARING NON-INVASIVE VENTILATION METHODS IN RESPIRATORY SUPPORT OF PRETERM NEONATES WITH RESPIRATORY DISEASES • A.S. Farhat, A. Mohammadzadeh, G.A. Mamuri, R. Saeidi, S. Noorizadeh ABS 5. PREDICTORS AND OUTCOMES OF CONTINUOUS POSITIVE AIRWAY PRESSURE AND NASAL HIGH-FLOW TREATMENT FAILURE IN PRETERM INFANTS: A SECONDARY ANALYSIS OF A RANDOMIZED TRIAL • B. Manley, C. Roberts, D. Frøisland, L. Doyle, P. Davis, L. Owen ABS 6. NEONATAL NON-INVASIVE RESPIRATORY SUPPORT APPROACH: A TWO COUNTRIES COMPARISON • I. Bresesti, S. Zivanovic, G. Lista, C. Roehr ABS 7. PREDICTORS OF EARLY CPAP FAILURE IN VERY LOW BIRTH WEIGHT PRETERM INFANTS • W.A. Gonçalves-Ferri, F.P. Martins-Celini, G.H. Seribeli, E. Sacramento, C. Calixto, M. Bertoldi, D.C. Aragon ABS 8. CHARACTERIZATION OF PORACTANT ALFA AND BUDESONIDE EXTEMPORANEOUS COMBINATION FOR SAFE AND EFFECTIVE INTRATRACHEAL ADMINISTRATION • F. Ricci, C. Catozzi, F. Ravanetti, F. D’Aló, N. Machidani, E. Sgarbi, V. Di Lallo, F. Saccani, M. Pertile, A. Cacchioli, P. Puccini, S. Catinella, G. Villetti, M. Civelli, F. Amadei, G. Aquino, F.F. Stellari, B. Pioselli, F. Salomone ABS 9. LENGTH OF MECHANICAL VENTILATION AND CLINICAL FEATURES AT BIRTH IN PREMATURE INFANTS • A.M. Nakato, R.P.G.V.C. Silva, N. Rosario Filho ABS 10. CONGENITAL LOBAR EMPHYSEMA MISDIAGNOSED AS PNEUMOTHORAX • I. Bakalli, E. Kola, R. Lluka, E. Celaj, D. Sala, I. Gjeta, S. Sallabanda ABS 11. SECRETORY PHOSPHOLIPASE A2 AND INFLAMMATION PROFILE IN PRETERM BABIES WITH RDS RECEIVING ONE OR MULTIPLE SURFACTANT DOSES • S. Shankar-Aguilera, C. Fitting, L. Vedovelli, V. Dell’Orto, V.P. Carnielli, L. Touqui, D. De Luca, M. Simonato ABS 12. SURFACTANT ADMINISTRATION AND NON-INVASIVE VENTILATION IN SURFACTANT DEFICIENCY NEWBORN PIGLETS • C. Rey-Santano, V. Mielgo, M. Gomez-Solaetxe, F. Ricci, F. Bianco, F. Salomone, B. Loureiro, J. López-de-Heredia ABS 13. THE EFFECT OF MINIMALLY INVASIVE SURFACTANT THERAPY ON DIAPHRAGMATIC ACTIVITY • C.G. de Waal, G.J. Hutten, F.H.C. de Jongh, A.H.L.C. van Kaam ABS 14. RELIABILITY AND ACCURACY OF PULSE OXIMETRY TO DETERMINE SaO2 AND PaO2 IN PRETERM INFANTS • D. Wackernagel, M. Blennow, A. Hellström ABS 15. CAN WE ASSESS THE SEVERITY OF NEONATAL RESPIRATORY DISTRESS BY ULTRASOUND? A COMPARISON OF THREE METHODS • F. Raimondi, F. Migliaro, L. Verdoliva, D. Gragnaniello, G. Poggi, C. Sansone, R. Kosova, L. Capasso ABS 16. MATERNAL PREECLAMPSIA AND THE RISK OF RESPIRATORY DISTRESS SYNDROME IN VLBW INFANTS • T.A. Yen, Y.H. Wen, H.I. Yang, W.S. Hsieh, H.C. Chou, C.Y. Chen, K.I. Tsou, P.N. Tsao ABS 17. EFFECT OF COMMERCIALLY AVAILABLE SURFACTANTS ON MORTALITY AND RESPIRATORY OUTCOMES IN PRETERM NEONATES WITH RDS: SYSTEMATIC REVIEWS AND META-ANALYSIS • L. De Martino, D. De Luca ABS 18. A CLINICAL CASE OF A CHILD WITH CONGENITAL CENTRAL HYPOVENTILATION SYNDROME (CCHS) IN THE EARLY NEONATAL PERIOD • R. Maslarska, M. Kalaydzhieva, S. Deneva, V. Konstantinova, S. Kontilska, I. Ilieva, J. Ivanova, V. Ivanova, E. Kerinova, R. Georgieva, T. Todorov ABS 19. HEALTHCARE BURDEN OF BRONCHOPULMONARY DYSPLASIA AMONG EXTREMELY PRETERM INFANTS IN THE UNITED STATES • M. Mowitz, S. Sarda, A. Mangili, R. Ayyagari, W. Gao, J. Zhao ABS 20. NCPAP PRESSURE AT INITIATION: IS HIGHER PRESSURE BETTER? • S. Bhisikar, S. Goel, S. Manerkar, J. Mondkar ABS 21. TRANSPORT OF HIGH-RISK NEONATES WITH RESPIRATORY FAILURE: A SINGLE CENTER COHORT ANALYSIS BASED ON THE TRANSPORT RISK INDEX OF PHYSIOLOGIC STABILITY VERSION II (TRIPS-II) • M. Klemme, A. Staffler, K.M. Förster, A. Schulze, S. Herber-Jonat, J. Kappeler, A.W. Flemmer ABS 22. RETROSPECTIVE AUDIT OF POSTNATAL OUTCOME OF ANTENATALLY DIAGNOSED RENAL PELVIS DILATATION • S. Vora, N. Kavalloor, T.L. Yap, P.C. Khoo, V. Rajadurai ABS 23. CONTINUOUS POSITIVE AIRWAY PRESSURE IS NOT WELL TRANSMITTED DURING LESS INVASIVE SURFACTANT ADMINISTRATION: A PHYSIOLOGIC STUDY • G. Jourdain, M. De Tersant, V. Dell’Orto, G. Conti, D. De Luca ABS 24. TGFβ SIGNALING IS CRITICAL FOR REGULATING A PROXIMAL DIFFERENTIATION PROGRAM AND LUNG BRANCHING MORPHOGENESIS THROUGH ACTIVATING NOTCH SIGNALING • P.N. Tsao, H.K. Chen, T.Y. Ling, W.V. Cardoso ABS 25. CHANGES IN EXPRESSION OF CONNECTIVE TISSUE GROWTH FACTOR (CTGF) IN NEWBORN RAT LUNGS AFTER VENTILATION • A. Remesal, E. Gutierrez, L. San Feliciano, M. Mateos, A. García-Sánchez, M. Isidoro-García, D. Ludeña ABS 26. ANTENATAL GLUCOCORTICOIDS ATTENUATE CHANGES BY VENTILATION IN EXPRESSION OF CONNECTIVE TISSUE GROWTH FACTOR (CTGF) IN NEWBORN RAT LUNG • M. Mateos, E. Gutierrez, L. San Feliciano, A. Remesal, M. Isidoro-García, A. García-Sánchez, D. Ludeña ABS 27. RELATIONSHIP BETWEEN SECRETORY PHOSPHOLIPASE A2 PATHWAY AND SHORT TERM OUTCOMES IN PRETERM NEONATES WITH RDS • S. Shankar-Aguilera, C. Fitting, R. Raschetti, M. Sminato, V. Dell’Orto, L. Vedovili, V.P. Carnielli, L. Touqui, D. De Luca ABS 28. THE EFFECT OF ANTENATAL STEROID ON DIFFERENT GESTATIONAL AGE OF VLBW INFANT – A POPULATION STUDY • Y.T. Chen, S.Y. Liu, H.I. Yang, C.Y. Chen, H.C. Chou, W.S. Hsieh, K.I. Tsou, P.N. Tsao ABS 29. IDENTIFICATION OF A REGULATORY ALVEOGENESIS GENE CLUSTER USING A NOVEL GENETIC APPROACH • F. Gao, C. Li, R. Ramanathan, P. Minoo ABS 30. A COST IMPROVEMENT PROJECT: REVIEW OF THE USE OF INHALED NITRIC OXIDE (iNO) IN A NEONATAL INTENSIVE CARE • B. Zanetti, R. Roy ABS 31. IMPROVED SURVIVAL AND DECREASED INCIDENCE OF BRONCHOPULMONARY DYSPLASIA IN INFANTS LESS THAN 27 WEEKS GESTATION AFTER A RESPIRATORY CARE BUNDLE • J. Soliz, A. Soliz ABS 32. VOLUME-TARGETED VERSUS PRESSURE-LIMITED VENTILATION IN NEONATES – A COCHRANE SYSTEMATIC REVIEW AND META-ANALYSIS UPDATED 2017 • C. Klingenberg, K.I. Wheeler, N. McCallion, C.J. Morley, P.G. Davis ABS 33. OXYGEN SATURATION TARGETING USING AUTOMATED VERSUS MANUAL CONTROL OF INSPIRED OXYGEN IN PRETERM INFANTS: A SYSTEMATIC REVIEW AND META-ANALYSIS • S. Mitra, B. Singh, W. El-Naggar, D. McMillan ABS 34. DROPS IN SATURATION AND HEART RATE IN HEALTHY NEWBORNS: MORE THAN WE THINK • S.J.A. Balink, R.C.J. de Jonge, T.G. Goos, R.H.T. van Beek ABS 35. LUNG FUNCTION AND IgE RESPONSE ARE REDUCED IN 9 TO 10 YEARS OLD ASTHMATIC CHILDREN WITH PRETERM BIRTH • L.C. Fang, J.Y. Wang, S.D. Shyur, S.H. Chu, Y.H. Kao, W.T. Lei ABS 36. TRANSFUSION-RELATED ACUTE LUNG INJURY IN PRETERM INFANTS IN THE NEONATAL INTENSIVE CARE • M. van Tuyl, L. Snoek, R.M. Wösten-van Asperen, A.H.L.C. van Kaam, W. Onland ABS 37. PRETERM BIRTH REDUCES ATOPIC SENSITIZATION IN PRESCHOOL CHILDREN WITH ALLERGIC DISEASE • J.Y. Wang, L.C. Fang ABS 38. THE INCIDENCE OF RESPIRATORY MORBIDITY IN LATE PRETERM INFANT • G. Olariu, S. Olariu, M. Tunescu ABS 39. HELPING BABIES BREATHE, SECOND EDITION: STRENGTHENING THE PROGRAM TO INCREASE GLOBAL NEWBORN SURVIVAL • B. Kamath-Rayne, M. Visick, W. Keenan, G. Little, N. Singhal, S. Niermeyer ABS 40. EXPRESSION OF THE HYALURONAN RECEPTOR RHAMM IN BRONCHIOLAR EPITHELIUM OF NEONATES NEGATIVELY CORRELATES WITH AIR CONTENT IN THE LUNG • L. Markasz, G. Sedin, R.C. Savani, R. Sindelar ABS 41. SUDDEN VERSUS PRESSURE WEAN FROM NASAL CPAP IN VERY PRETERM INFANTS: A MULTICENTER RANDOMIZED CONTROLLED TRIAL • C.F. Jensen, F. Ebbesen, A.S. Sørensen, T.B. Henriksen ABS 42. BIPAP REDUCES EXTUBATION FAILURE IN THE FIRST WEEK COMPARED TO CPAP IN NEONATES < 30 WEEK OF GESTATIONAL AGE WITHOUT INCREASED RISK OF PNEUMOTHORAX • L. Capasso, A.C. Borrelli, M.A. Caiazzo, C. Parrella, R. Albachiara, F. Raimondi ABS 43. RISK FACTORS ASSOCIATED WITH CPAP FAILURE IN VERY LOW BIRTH WEIGHT INFANTS • D. Dobryanskyy, O. Borysiuk, L. Sekretar, S.Yaremchuk, S. Vereshchak, Z. Salabay ABS 44. EFFECTS OF PASSIVE SMOKING ON LUNG FUNCTION TESTS IN PRESCHOOL CHILDREN BORN LATE-PRETERM • A. Günlemez, I. Er, C. Baydemir, A.E. Arısoy, A.S. Gökalp ABS 45. THE EFFECT OF SUSTAINED LUNG INFLATION ON EARLY RESPIRATORY OUTCOMES IN TERM INFANTS • M. Cetinkaya, D. Kilic, S.Y. Semerci, B. Cebeci, O. Saglam ABS 46. PCO2 LEVELS AND CLINICAL AND NEURODEVELOPMENTAL OUTCOMES OF EXTREMELY LOW BIRTH WEIGHT INFANTS • U.H. Thome, J. Dreyhaupt, O. Genzel-Boroviczeny, B. Bohnhorst, M. Schmid, H. Fuchs, O. Rohde, S. Avenarius, H.G. Topf, A. Zimmermann, D. Faas, K. Timme, B. Kleinlein, H. Buxmann, W. Schenk, H. Segerer, N. Teig, F. Pulzer, R. Hentschel, M. Heckmann, R. Schlösser, J. Peters, R. Rossi, W. Rascher, R. Böttger, J. Seidenberg, G. Hansen, M. Zernickel, R. Muche, H.D. Hummler, for the PHELBI Study Group ABS 47. AIR RETRIEVAL OF A NEWBORN BABY BORN WITH SEVERE CONGENITAL CARDIAC DEFECT • B. Carter, J. Tan, D. Wagh, J. Davis, R. Pal ABS 48. COMPARISON OF NIPPV AND NCPAP FOR THE MANAGEMENT OF RDS BY USING INSURE APPROACH IN PRETERM INFANTS • S.A. Ozdemir, E.Y. Ergon, R. Çolak, M. Yıldız, F. Kulalı, K. Çelik, Ö. Olukman, Ş. Çalkavur ABS 49. PERINATAL FACTORS ASSOCIATED TO THE FAILURE OF EARLY NASAL CONTINUOUS POSITIVE PRESSURE IN VERY LOW BIRTH WEIGHT INFANTS • T.S. Souza, A.A.Vieira, C. Morcelli-Tovar ABS 50. VENTFIRST: A MULTICENTER RCT OF ASSISTED VENTILATION DURING DELAYED CORD CLAMPING FOR EXTREMELY PRETERM INFANTS • K. Fairchild, S. Niermeyer, J. Winter, C. Chisholm, J. Kattwinkel, on behalf of the Vent First Steering Committee (J. Fang, C. Colby – Mayo Clinic; J. Barry – University of Colorado; M. Al-Hosni, M. Strand – St. Louis University; T. Gorman, L. vanMarter – Brigham and Women’s Hospital; R. Schelonka, J. Warren – Oregon Health Sciences University; S. Thomas – University of Calgary; G. Schmolzer – University of Alberta; A. Camblos, S. Fowler, M. Haynes, G. Petroni, M. Thielen – University of Virginia) ABS 51. IS THE DOUBLE LUNG POINT AN ACCURATE DIAGNOSTIC MARKER FOR TRANSIENT TACHYPNEA OF THE NEONATE? A PROSPECTIVE, INTERNATIONAL STUDY • F. Migliaro, N. Yousef, J. Rodriguez Fanjul, D. De Luca, I. Corsini, C. Dani, V. Di Guardo, M. Giampietri, L. Capasso, A. Sodano, F. Raimondi ABS 52. BEDSIDE LUNG ULTRASONOGRAPHY FOR THE DIAGNOSIS OF NEONATAL RESPIRATORY DISTRESS IN THE FIRST 24 HOURS OF LIFE • I. Corsini, N. Parri, E. Gozzini, C. Coviello, V. Leonardi, C. Poggi, M. Giacalone, T. Bianconi, L. Tofani, C. Dani ABS 53. IMPACT OF THE USE OF HIGH POSITIVE END EXPIRATORY PRESSURE ON EXTUBATION OF PREMATURE INFANTS WITH SEVERE BRONCHOPULMONARY DYSPLASIA • W.A. Gonçalves-Ferri, F. Pereira Martins-Celini, C. Danieli Troiano, D.C. Aragon ABS 54. THE USE OF DEXAMETHASONE IN PRETERM INFANTS FOR LUNG DISEASE IN A TERTIARY NICU • K.M. Sun, H. Gowda ABS 55. CONSULTANT PRESENCE AT DELIVERY: A RETROSPECTIVE AUDIT OF DEMOGRAPHICS AND OUTCOMES IN A TERTIARY UK CENTRE • L. Mahoney, T. Hunt, H. Rabe, P. Amess, N. Aiton, N. Bhat, R. Bomont, N. Drenchev, C. Garland, C. Lawn, B. Reulecke, R. Watkins, R. Fernandez ABS 56. THE COMPARISON OF HEATED HUMIDIFIED HIGH-FLOW NASAL CANNULA VERSUS NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE FOR RESPIRATORY SUPPORT IN NICU • K.Y. Chao, C.E. Chiang, Y.L. Chen, L.Y. Tsai, Y.H. Chien, S.C. Mu ABS 57. COMPARISON BETWEEN OUTCOMES OF MINIMALLY INVASIVE TECHNIQUE AND INTUBATION SURFACTANT EXTUBATION IN PRETERM INFANTS LESS THAN 1,500 GRAMS IN A DEVELOPING COUNTRY • W.A. Gonçalves-Ferri, P. Paiva, L. Scalioni, E. Sacramento, C. Calixto, A.C. Hallak, D.C. Aragon ABS 58. PREMATURE INFANTS WITH VERY LOW WEIGHT WITH APNEA HAVE POOR RESULTS DESPITE TREATMENT • A.B. Gonçalves, M.M. Lourenço, L. Scacioli, E. Sacramento, C. Calixto, D.C. Aragon, W.A. Gonçalves-Ferri ABS 59. BOCHDALEK HERNIA WITH INTRATHORACIC KIDNEY ASSOCIATED WITH AORTIC COARCTATION • B. Skenderi Mustafa, H. Ismaili, F. Kajtazi, G. Hazbahta, F. Krasniqi ABS 60. INHALED NITRIC OXIDE IN CONGENITAL DIAPHRAGMATIC HERNIA – RESULTS FROM THE EUROPEAN INHALED NITRIC OXIDE REGISTRY • R. Kettle, N.V. Subhedar ABS 61. EARLY HIGH FREQUENCY VENTILATION – A PROMISE OF PROTECTIVE VENTILATION? • W.A. Gonçalves-Ferri, M. Bertoldi, A.B. Gonçalves, E. Sacramento, C. Calixto, D.C. Aragon ABS 62. INHALED NITRIC OXIDE AND PRETERMS: DOOM, GLOOM OR RIGHT? 11 YEARS’ EXPERIENCE AT TERTIARY CENTRE • E. Syrimi, H. Warwick, P. Satodia, P. Nath ABS 63. IS APGAR SCORE A PREDICTOR OF SEVERITY IN PRETERM INFANTS? • W.A. Gonçalves-Ferri, P.P. Paiva, A.B. Gouvea, E. Sacramento, C. Calixto, D.C. Aragon ABS 64. CURRENT PRACTICE OF NEURALLY ADJUSTED VENTILATOR ASSIST IN THE NEONATAL INTENSIVE CARE UNIT: A TAIWAN SURVEY • C.E. Chiang, Y.L. Chen, L.Y. Tsai, Y.H. Chien, S.C. Mu, K.Y. Chao ABS 65. LUNG ULTRASOUND FOR THE DIAGNOSIS OF PULMONARY CONSOLIDATIONS IN PATIENTS WITH BRONCHOPULMONARY DYSPLASIA • I. Koltunov, M. Degtyareva, A. Mazaev, A. Gorbunov, A. Erokhina ABS 66. NON-INVASIVE HIGH FREQUENCY OSCILLATORY VENTILATION IN PRETERM INFANTS: A RANDOMISED CONTROLLED CROSSOVER TRIAL • D. Klotz, H. Schneider, S. Schumann, B. Mayer, H. Fuchs ABS 67. THE EFFECT OF HYDROCHLOROTHIAZIDE WITH SPIRONOLACTONE TREATMENT ON BRONCHOPULMONARY DYSPLASIA DEVELOPMENT IN VERY-LOW-BIRTH-WEIGHT INFANTS • M. Buyuktiryaki, E. Alyamac Dizdar, N. Uras, N. Okur, O. Ertekin, S.S. Oguz ABS 68. OUTCOMES OF POSTNATAL HYDROCORTISONE THERAPY IN PRETERM INFANTS WITH BRONCHOPULMONARY DYSPLASIA: EXPERIENCE IN A TERTIARY CENTER • M. Buyuktiryaki, E. Alyamac Dizdar, N. Okur, H. Bezirganoglu, F.N. Sari, N. Uras, F.E. Canpolat, S.S. Oguz ABS 69. NONINVASIVE RESPIRATORY SUPPORT VIA NASAL CANNULA IN PREMATURE INFANTS: IS IT REALLY SAFE? • M. Buyuktiryaki, N. Okur, G. Kadioglu Simsek, H.G.Kanmaz, F.E. Canpolat ABS 70. THE LARYNGEAL MASK AIRWAY AND ITS USE IN NEONATAL RESUSCITATION – A CRITICAL REVIEW OF WHERE WE ARE IN 2017 • S.C. Bansal, S. Caoci, D. Trevisanuto, C.C. Roehr, E.M. Dempsey ABS 71. BRADYPREM STUDY: IS HEART RATE THE MOST VITAL OF ALL VITAL SIGNS DURING PRETERM RESUSCITATION? • V. Kapadia, J. Oei, O. Saugstad, Y. Rabi, N. Finer, I. Wright, W. Tarnow-Mordi, W. Rich, D. Rook, J. Smyth, K. Lui, S. Brown, M. Vento ABS 72. PHYSIOLOGICAL BASIS OF THE NICHD BPD CLASSIFICATION: A PROSPECTIVE OBSERVATIONAL STUDY IN VERY PRETERM INFANTS • J. Svedenkrans, B. Stoecklin, J.G. Jones, A.W. Gill, D. Doherty, J.J. Pillow ABS 73. USING THE COMBINATION OF SURFACTANT AND BUDESONIDE IN THE PREVENTION OF CHRONIC LUNG DISEASE IN PRETERM INFANTS WITH RDS • O. Sapun, E. Kleshchenko, O. Shishkina, T. Senyuk, N. Petrukhina, D. Kryuchko ABS 74. NASAL TRAUMA IN PRETERM INFANTS RECEIVING BINASAL NON-INVASIVE RESPIRATORY SUPPORT: A SYSTEMATIC REVIEW • D. Imbulana, B. Manley, P. Davis, L. Owen ABS 75. EVALUATION OF EFFECT OF CAFFEINE ONSET TIME ON SURFACTANT SYNTHESIS OF PREMATURE INFANTS ≤ 30 WEEKS OF GESTATIONAL AGE WITH RESPIRATORY DISTRESS • N. Okur, M. Buyuktiryaki, H. Bezirganoglu, O. Ertekin, E.D. Alyamac, F.E. Canpolat, S.S. Oguz ABS 76. OCTREOTIDE FOR CHYLOTHORAX? A SYSTEMATIC APPROACH TO ANSWERING THE QUESTION • G. Zuanetti, G. Cavallaro, G. Raffaeli, M. Colnaghi, F. Ciralli, I. Amodeo, S. Gulden, E. Leva, L. Pugni, F. Mosca ABS 77. PERINATAL INFLAMMATION AND INTRAUTERINE GROWTH RETARDATION ARE BOTH ASSOCIATED WITH LUNG FUNCTION IMPAIRMENT AT 12 YEARS OF AGE IN VERY PRETERM INFANTS • C. Hagman, L.J. Björklund, E. Tufvesson, I. Hansen Pupp ABS 78. ALVEOLAR SURFACTANT COMPOSITION IN PRETERM INFANTS WITH RESPIRATORY DISTRESS SYNDROME BEFORE EXOGENOUS SURFACTANT ADMINISTRATION: EFFECT OF GESTATIONAL AGE AND INFLAMMATION • G. Verlato, M. Simonato, E. Bassi, M. Fantinato, A. Correani, I. Giretti, E. Baraldi, P. Cogo, V. Carnielli ABS 79. BLOOD GLUCOSE LEVEL AND CEREBRAL OXYGENATION IN NEONATES IMMEDIATELY AFTER BIRTH • B. Urlesberger, Ch. Matterberger, N. Baik-Schneditz, B. Schwaberger, G.M. Schmölzer, L. Mileder, G. Pichler ABS 80. EARLY PREDICTIVE FACTORS FOR INSURE FAILURE IN THE MANAGEMENT OF PRETERM INFANTS WITH NEONATAL RESPIRATORY DISTRESS SYNDROME: A SYSTEMATIC REVIEW • B. De Bisschop, F. Derriks, F. Cools ABS 81. OUTCOMES OF POSTNATAL DEXAMETHASONE USE IN EXTREME PRETERM NEONATES IN A TERTIARY NEONATAL UNIT • A. Holt, L. Osborne, P. Satodia ABS 82. A RANDOMISED CONTROLLED TRIAL OF NEEDLE ASPIRATION OR CHEST DRAIN INSERTION FOR PNEUMOTHORAX IN NEWBORNS (THE NORD TRIAL), ISRCTN65161530 • M. Murphy, C. Heiring, N. Doglioni, D. Trevisanuto, M. Blennow, K. Bohlin, G. Lista, I. Stucchi, C. O’Donnell ABS 83. VALIDATION OF A TRANSCUTANEOUS TCPO2/TCPCO2 SENSOR WITH AN OPTICAL OXYGEN MEASUREMENT IN PRETERM NEONATES • W. van Weteringen, T.G. Goos, T. van Essen, N.H. Gangaram-Panday, R.C.J. de Jonge, I.K.M. Reiss ABS 84. SUCCESSFUL VENTILATION VIA ACCIDENTAL OESOPHAGEAL INTUBATION IN A CASE OF FLOYD TYPE III/FARO TYPE B TRACHEAL AGENESIS IN A DISCORDANT MONOZYGOTIC TWIN • M. Noureldein, A. Olariu, J. Egyepong ABS 85. PROTOCOLIZED WEANING IN MECHANICAL VENTILATION • B. Bol, H. van Zanten, J. Wielenga, A. vd Hoogen, P. Mansvelt, B. Blackwood, O.K. Helder ABS 86. WHAT IS THE IDEAL TARGET PRETERM POPULATION THAT MIGHT BENEFIT FROM THE EXPENSIVE PALIVIZUMAB PROPHYLAXIS? • S. Tsilika, D. Batra ABS 87. EVALUATION OF OXIDATIVE STRESS IN NEONATES • M. Matyas, M. Hășmășanu, D. Leucuta, L. Blaga, G. Zaharie ABS 88. ACCURACY OF OBTAINING NEONATAL HEART RATE FROM A NOVEL HAT MOUNTED, GREEN WAVELENGTH OPTICAL DEVICE • C. Henry, L. Shipley, C. Ward, S. Mirahamdi, B. Hayes-Gill, J. Carpenter, D. McCartney, D. Sharkey ABS 89. EFFECTS OF SURFACTANT REPLACEMENT THERAPY WITH PORCINE VS. BOVINE PREPARATIONS ON CEREBRAL OXYGENATION AND BIOELECTRIC ACTIVITY OF PRETERM INFANTS • T. Szczapa, L. Karpinski, H. Szczapa-Krenz, B. Witoslaw, A. Adamczak, J. Moczko, I. Miechowicz, P. Niedbalski, J. Gadzinowski, J. Mazela ABS 90. INCIDENCE AND OUTCOME OF PNEUMOTHORACES IN A TERTIARY NEONATAL INTENSIVE CARE UNIT • R.C. Ramaswamy, M.K. Brom, S.V. Rasiah ABS 91. CLINICAL IMPACT OF THE RESPIRATORY SYNCYTIAL VIRUS INFECTION IN INFANTS WITH A HISTORY OF PREMATURITY BETWEEN 32-34 WEEKS • N. Ramos, C.M. Martín, G. Uclés, R.C. Raynero, I. Pérez, M. González-Valcárcel, M.D. Sánchez-Redondo, A. Pantoja, J. Cobas, A. Escobar, A. Martínez ABS 92. VOLUME CONTROLLED OR VOLUME GUARANTEE VENTILATION IN PRETERM INFANTS: A RANDOMISED CONTROLLED TRIAL • H. Chitty, W. Tin, D. Stocken, R. Agbeko, J. Vormoor, S. Sinha ABS 93. LATE PRETERM INFANTS: WHAT IS THEIR REAL RESPIRATORY MORBIDITY? • A.M. Gil Fenoy, F.J. Pacheco Sánchez La Fuente, P. Miranda Romera, L. Serrano López, E. Martín Álvarez, J.A. Hurtado Suazo ABS 94. REVIEW OF OUTCOMES IN PRETERM NEONATES FOLLOWING CHANGE OF VENTILATORY PRACTICE TO VOLUME-TARGETED VENTILATION IN A NEONATAL INTENSIVE CARE UNIT • I. Fernando, H. McDermott, A. Singh, S. Rasiah ABS 95. OXYGEN SATURATION TRENDS IN LATE PRETERM INFANTS • L.Z.J. Williams, D. McNamara, J.M. Alsweiler ABS 96. INHALED NITRIC OXIDE IMPROVES SURVIVAL IN PRETERM INFANTS DIAGNOSED WITH PULMONARY HYPOPLASIA • K. Ellsworth, M. Ellsworth, L. Sangaralingham, R. Clark, G. Asay, C. Colby, W.A. Carey ABS 97. NORMALISATION OF PULMONARY GAS EXCHANGE CAPACITY IN VERY PRETERM INFANTS FOLLOWING INITIAL HOSPITAL DISCHARGE DEFINED BY SHIFT OF THE SPO2-PIO2 CURVE • Y.J. Choi, B. Stoecklin, J.J. Pillow ABS 98. SIMPLIFIED AUSTRALIAN AND NEW ZEALAND NEONATAL NETWORK (ANZNN) SHIFT TEST ACCURATELY PREDICTS RIGHTWARD SHIFT OF THE SPO2-PIO2 CURVE IN AN EXTREMELY PRETERM INFANT POPULATION • Y.J. Choi, B. Stoecklin, M.A. Hakeem, P. Woods, J.J. Pillow ABS 99. CORRELATION BETWEEN BODY TEMPERATURE AND CEREBRAL OXYGENATION IN NEONATES DURING TRANSITION AFTER BIRTH • L.P. Mileder, A. Richter, N. Baik-Schneditz, B. Schwaberger, C. Binder-Heschl, B. Urlesberger, G. Pichler ABS 100. A NEONATAL RESUSCITATION ALGORITHM FOR MID-TO-LOW RESOURCE SETTINGS IN MÉDECINS SANS FRONTIÈRES’ PROGRAMS • L. Umphrey, M. Blennow, M. Breindahl, A. Brown, O. Saugstad, M. ThioLluch, D. Trevisanuto, C. Roehr ABS 101. NASAL HIGH-FLOW THERAPY AS PRIMARY RESPIRATORY SUPPORT FOR PRETERM INFANTS WITHOUT USE OF NASAL CONTINUOUS POSITIVE AIRWAYS PRESSURE • S. Zivanovic, A. Scrivens, R. Panza, P. Reynolds, K. Ives, N. Laforgia, C.C. Roehr ABS 102. DIURETICS FOR EVOLVING CHRONIC LUNG DISEASE OF PREMATURITY: WHO ARE WE TREATING? • A.K. Linklater, R. Cuzzilla, S.E. Jacobs ABS 103. NEO (NEONATAL ESOPHAGEAL OBSERVATION) TUBE – A FEEDING TUBE WITH MONITORING FUNCTION • P. Simmen, B. Jesacher, P.-A. Tran, L. Suter, A. Haeberlin, S.M. Schulzke, T. Niederhauser, K. Jost ABS 104. CAN TcPCO2 MONITORIZATION IN THE DELIVERY ROOM BE HELPFUL FOR DIFFERENTIATING TERM NEWBORNS IN NEED OF HOSPITALIZATION FOR RESPIRATORY MORBIDITIES? • I. Mungan Akin, E. Bocu, M. Uygun, S. Sevuk Ozumut, D. Buyukkayhan, S. Arslanoglu, F. Ovali ABS 105. HIGH FREQUENCY OSCILLATORY VENTILATION COMBINED WITH VOLUME GUARANTEE USING VERY LOW TIDAL VOLUMES TO PREVENT LUNG DAMAGE IN IMMATURE NEWBORNS • N. González-Pacheco, A. Rodríguez-Sánchez de la Blanca, C. Ramos-Navarro, M. Velilla-Aparicio, I. Marsinyach-Ros, I. Pescador-Chamorro, M. Sánchez-Luna ABS 106. MANAGEMENT OF PNEUMOTHORAX IN NEWBORNS: A NEONATAL INTENSIVE CARE UNIT EXPERIENCE IN TUNISIA • K. Ben Ameur, T. Khemis, A. Ben Salem, H. Ben Hamida, F.Z. Chioukh, K. Monastiri ABS 107. THE SAFE PROTOCOL: A SONOGRAPHIC ALGORITHM FOR LIFE-THREATENING EMERGENCIES IN THE NEONATAL INTENSIVE CARE UNIT • N. Yousef, S. Shankar-Aguilera, D. De Luca ABS 108. MACROLIDE THERAPY AND INCREASED PATENT DUCTUS ARTERIOSUS TREATMENT IN UREAPLASMA-POSITIVE PREMATURE INFANTS • S. Kim, E. Jung, H. Kim, W.S. Song, J.H. Hwang, C.Y. Kim, B.S. Lee, E.A.-R. Kim, K.-S. Kim ABS 109. MALIGNANT PERTUSSIS. IS IT TIME FOR EXCHANGE TRANSFUSION? • R. Roldán, M. Huescar, M.G. Espinosa, A. Morales, E. Salguero ABS 110. DELAYED CORD CLAMPING DURING RESUSCITATION – A RANDOMIZED TRIAL • O. Andersson, A. KC, N. Rana, U. Ewald, M. Målqvist ABS 111. PERI-OPERATIVE MANAGEMENT OF NEONATES WITH ESOPHAGEAL ATRESIA IN LOW-INCOME COUNTRIES: EXPERIENCE OF TUNISIA • F.Z. Chioukh, K. Ben Ameur, T. Khemis, A. Ksia, A. Ben Salem, H. Ben Hamida, K. Monastiri ABS 112. LESS INVASIVE SURFACTANT ADMINISTRATION IN PRETERM INFANTS. REVIEW AFTER 4 YEARS OF IMPLEMENTATION • C. Ramos-Navarro, S. Zeballos-Sarrato, N. Gonzalez-Pacheco, A. Rodriguez-De la Blanca, M. Arriaga-Redondo, S. Villar-Castro, I. Pescador-Chamorro, N. Navarro-Patiño ABS 113. COMPARISON OF RSV HOSPITALISATION IN PRETERM INFANTS WITH CHRONIC LUNG DISEASE WHO DO NOT QUALIFY FOR PALIVIZUMAB PROPHYLAXIS WITH THOSE WHO QUALIFY IN NOTTINGHAM, UK • S. Tsilika, D. Batra ABS 114. AN UNUSUAL CAUSE OF RESPIRATORY DISTRESS IN NEONATES: CONGENITAL PULMONARY LYMPHANGIECTASIA (TWO CASE REPORTS) • S. Nouri Merchaoui, N. Mahdhaoui, H. Ayache, M. Bellalah, I. Kacem, H. Barbouche, A. Ghith, M.T. Yacoubi, J. Methlouthi, H. Seboui ABS 115. ETIOLOGICAL AND PATHOLOGICAL CORRELATIONS IN PERSISTENT PULMONARY HYPERTENSION OF THE NEWBORN • M.L. Ognean, R. Dumitra, O. Boantă, C. Zgârcea, E. Olariu, S. Kovacs ABS 116. BRONCHOPULMONARY DYSPLASIA – ARE THERE NEW RISK FACTORS IN VERY PRETERM INFANTS? • M.L. Ognean, O. Boantă, E. Olariu, S. Kovacs, C. Zgârcea, R. Dumitra, D. Andreicuţ ABS 117. OUTCOMES OF PRETERM INFANTS LESS THAN 26 WEEKS GESTATION AT BIRTH WHO RECEIVED CHEST COMPRESSION OR ADRENALINE DURING RESUSCITATION AT BIRTH • H. Shing, H. Gowda ABS 118. EVALUATION OF SURFACTANT DOSE ADMINISTERED IN CLINICAL PRACTICE FOR THE TREATMENT OF RESPIRATORY DISTRESS SYNDROME (RDS): RETROSPECTIVE OBSERVATIONAL STUDY. SURPRAIS STUDY • H. Boix, D. Elorza, S. Rite, L. Arruza, C. Fernández, I. Serrano, I. Baquedano, A. Sanchez, E. Ferreira, V. Martinez, P. Fernandez, R. Gonzalez ABS 119. LUNG ULTRASOUND TO ASSESS PERSISTENT PULMONARY HYPERTENSION OF THE NEWBORN ETIOLOGY • B. del Rey Hurtado de Mendoza, J. Moreno Hernando, J. Sánchez-de-Toledo, J. Rodríguez-Fanjul ABS 120. IMPROVEMENT OF FACE MASK VENTILATION TECHNIQUE USING A LIVE FEEDBACK SYSTEM • S. Bhayat, H. Gowda ABS 121. NEURALLY ADJUSTED VENTILATION IN PATIENTS WITH CONGENITAL DIAPHRAGMATIC HERNIA • A.M. Sanchez-Torres, H. Peinado, R. Madero, M.D. Elorza ABS 122. NON-INVASIVE NEURALLY ADJUSTED VENTILATION IN THE NEWBORN • H. Peinado, H. Sánchez-Torres, R. Madero, M.D. Elorza ABS 123. IMPACT OF PRETERM BIRTH ON RESPIRATORY MUSCLE FUNCTION IN CHILDHOOD • S. Fouzas, A. Vervenioti, G. Dimitriou ABS 124. THE NON-INVASIVE RESPIRATORY SUPPORT FAILURES IN PRETERM INFANTS. RISK FACTORS AND OUTCOMES • C. Ramos-Navarro, I. Marsinyach Ross, G. Zeballos-Sarrato, P. Chimenti-Camacho, A. Perez-Perez, R. Gregorio-Hernández, M. Sánchez-Luna ABS 125. SELECTIVE LUNG VENTILATION: A THERAPEUTIC STRATEGY FOR ACQUIRED LUNG COLLAPSE IN A TERM INFANT • H. Gowda, S. Bhayat ABS 126. SUDDEN UNEXPECTED COLLAPSE OF NEWBORN INFANTS: INCIDENCE, RISK FACTORS AND ROLE OF PERINATAL TRANSITION • E. Herlenius, D. Forsberg, G. Drevin, N.J. Pejovic ABS 127. INCIDENCE OF RESPIRATORY MORBIDITY IN LATE PRETERM AND TERM INFANTS IN RESPECT TO DELIVERY MODE • J. Gromann, T. Burkhardt, R. Arlettaz, S. Wellmann ABS 128. PREVENTION OF HYPOCAPNIA WITH INHALATIVE CO2 IN NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY – THE HENRIC STUDY • E. Szakmar, K. Kovacs, U. Meder, Cs. Andorka, K. Kaila, M. Szabo, A. Jermendy ABS 129. RISK FACTORS ASSOCIATED TO SURVIVAL FREE BRONCHOPULMONARY DYSPLASIA ACCORDING TO GESTATIONAL AGE • C. Ramos-Navarro, S. Zeballos-Sarrato, E. Sanz-Lopez, E. Maderuelo-Rodriguez, N. Gonzalez-Pacheco, M. Sánchez-Gómez de Orgaz, M. Sánchez-Luna ABS 130. OUTCOME OF INFANTS BORN AFTER MID-TRIMESTER RUPTURE OF MEMBRANES • T. Hurley, J. Miletin, A. Martin, C. Fitzpatrick, J. Semberova ABS 131. NEURALLY ADJUSTED MECHANICAL VENTILATION (MV-NAVA) IN THE NEWBORN • A.M. Sánchez Torres, H. Peinado, R. Madero, M.D. Elorza ABS 132. CHYLOTHORAX: CASE SERIES OF 20 YEARS • M. Rosário, A. Reis e Melo, S. Pissarra, G. Rocha, H. Guimarães ABS 133. NEONATAL CHYLOTHORAX: 20 YEARS EXPERIENCE IN A TERTIARY NEONATAL UNIT • H. Sharp, C. Kortsalioudaki, M. Sellwood, G. Kendall ABS 134. IN VITRO ANALYSES OF GASTRIC ASPIRATES FROM PRETERM NEONATES AFTER CORTICOSTEROID THERAPY • V. Milov, D. Manoylov, A. Jordanova, A. Tsanova, V. Stoyanova, E. Stoimenova, D. Petrova, E. Hristova, Z. Lalchev ABS 135. WHICH NASAL CPAP SYSTEM TO USE IN PRETERM NEWBORNS WITH RESPIRATORY DISTRESS SYNDROME • E. Jazexhiu-Postoli, E. Vevecka, E. Petrela, D. Bujari, E. Rapushi ABS 136. PREDICTIVE AND RISK FACTORS FOR EARLY NON-INVASIVE RESPIRATORY SUPPORT FAILURE IN A COHORT OF PRETERM INFANTS: A RETROSPECTIVE STUDY • I. Bresesti, F. Viaroli, F. Castoldi, F. Scopesi, B. Roviglione, L. Ramenghi, F. Cerritelli, G. Lista ABS 137. MEASURING OXYGEN DIFFUSION AT 36 WEEKS’ PMA IN PRETERM INFANTS: ANALYSIS OF THE SatO2/FIO2 RATIO AND ITS CORRELATION WITH EARLY RESPIRATORY PATTERNS OF DISEASE • S. Nobile, P. Marchionni, F. Porcarelli, A. Boria, V. Carnielli ABS 138. RELIABILITY OF MANUALLY COLLECTED CARDIO-PULMONARY PARAMETERS IN PATIENTS’ CHARTS • P. Marchionni, L. Scalise, L. Antognoli, S. Nobile, E. Tomasini, V. Carnielli ABS 139. ASSESSMENT OF CARDIO-RESPIRATORY RATES BY NON-INVASIVE MEASUREMENT METHODS IN HOSPITALIZED PRETERM NEONATES • L. Antognoli, P. Marchionni, L. Scalise, S. Nobile, E.P. Tomasini, V.P. Carnielli ABS 140. RESPIRATORY DISTRESS SYNDROME: GENETIC POLYMORPHISM OF GENES ENCODING SURFACTANT PROTEIN B AND XENOBIOTIC BIOTRANSFORMATION ENZYMES • G. Shishko, M. Artsiusheuskaya, A. Sukharava, E. Mikhalenka, K. Hamolko, I. Valentsiukevich, A. Kilchevski